TRAVAIL DU TEXTE EN COURS DE LANGUES ETRANGERES («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article discusses the ways and difficulties of developing competence to work on text when teaching French as a foreign language.
Keywords: text, difficulties, linguistic, communicative, sociocultural and intercultural competencies.